Boardroom electronic voting scheme based on DC-net - Long-hai LI; Shao-feng FU; Cheng-qiang HUANG (Tongxin xuebao)
A novel electronic voting scheme was proposed which was quite suitable for small scale election setting.An outstanding characteristic of the design was its guarantee of unconditionally perfect ballot secrecy.It satisfied self-tallying,fairness and verifiability.Disruption of the result of an election equals to breaking the discrete logarithm problem.The scheme is built on top of the DC-net (dining cryptographers network) anonymous broadcast protocol.It needs no trusted authority to guarantee its security,but assumes a complete network of private channels between voters.